La regulación de la eutanasia en nuestro código orgánico integral penal y sus consecuencias socio jurídicas - Vivar Cuji, Hernán René (2011)
Every day more voices are calling for legalization of euthanasia arise. So far it has been achieved in some countries something that is ethically acceptable. It has recognized the right of the patient to refuse extraordinary treatment and to die in peace and with dignity. Clearly, for many of the pro-euthanasia associations it is a first step towards a situation where euthanasia positive patients seeking an end to his life is also supported.